Understanding the Role of Different Actors in Preventing Human Trafficking:: The Bangladesh Experience - Awal, Mohammad Abdul (The Jahangirnagar Review, 2025)
Bangladesh serves as a crucial source and transit country for human trafficking in Southern Asia. The main kinds of human trafficking are forced labour and sexual exploitation. The trafficking victims originating from Bangladesh include males, females, and minors. Human trafficking is a pervasive problem in Bangladesh, necessitating the collaborative efforts of several stakeholders, including the government, non-governmental organisations (NGOs), and foreign entities. The government is facing challenges in implementing strategies to reduce the demand for commercial sex activities and child sex industries. The poor and chaotic governmental approaches to addressing human trafficking are greatly exacerbating the problem. There is an urgent need for more employment opportunities for the unemployed, improved productivity in the agricultural sector, and more rigorous enforcement of laws against illegal activities. Human trafficking negatively impacts women and children and damages the nation's image. Subsequent to their freeing, the hostages would experience psychological anguish and societal stigma. They need sufficient guidance and comprehension. The overpopulation problem in Bangladesh might be converted into a substantial labour force. Thus, the proficient implementation of policy and enforcement of legislation is essential. The article is written based on a review of important documents aimed at understanding the role of various players/actors, including the government of Bangladesh, in combating human trafficking after learning about the causes and consequences of human trafficking.